STILLNESS ATSCHOOL: WELL-BEING AFTER EIGHTWEEKS OF MEDITATION-BASED PRACTICE IN SECONDARYSCHOOL - Terjestam, Yvonne (Psyke & Logos, 2011)
<span lang="EN-US" style="color: #211d1e; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-bidi-theme-font: minor-latin; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-bidi-font-style: italic;">Stress-related psychological difficulties amongst youths are of major concern in Western countries. Causations are complex and not fully understood but school is known to be one major factor. Stress is well known to increase during adolescence and a WHO school-based study of some 120 000 students in 28 countries showed a threefold increase from the age of 11 to 15 years. Teachers in the modern classroom need means to handle contemporary problems in classroom milieus that are high in stress and low in concentration. <span lang="EN-US" style="color: #211d1e; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-bidi-theme-font: minor-latin; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-bidi-font-style: italic;">The aim of the present project was to study whether scheduled practice of a meditation-based technique for stillness affects pupils’ stress and general wellbeing at school. Some 400 pupils aged 12-15 years in Swedish schools were taking part in this pre-test, post-test study. Parallel classes were assigned to either <span lang="EN-US" style="color: #211d1e; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-bidi-theme-font: minor-latin; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-bidi-font-style: italic;">a control- or experiment group. A meditation based technique for inducing stillness was introduced and scheduled for practice in class three times a week during eight weeks in the experiment group. The control group received no intervention. All pupils completed a questionnaire individually in class before the intervention started (pre-test) and 10 weeks after (post-test). During this time the experiment group had practiced the technique for eight weeks. Testing for differences between groups showed no major differences between the control- and the experiment group. These results of ANOVA pre-test, post-test analysis revealed improvement on psychological difficulties measured by the total score of the "Strengths and difficulties questionnaire” (SDQ) as well as on the subscale "Emotional symptoms” (SDQ) in the experiment- but not control group. Furthermore, general stress level measured by "General stress scale” (GSC) was somewhat lower at post condition after stillness practice. Results showed no significant differences in pre-test, post-test scores in the experiment group as regards the scales "Psychological distress” (PD) or "Well-being at school” (WBS). Gender differences showed that girls but not boys in the experiment- but not the control group at post-test reported better well-being at school, less peer problems and less overall psychological difficulties. The results indicate that meditation-based techniques for stillness practices can have a positive effect on adolescent well- being when scheduled and practiced by pupils in class whereas the gender differences show that such techniques practiced in class during adolescence have different effects on girls’ wellbeing, compared to boys’. <span lang="EN-US" style="color: #211d1e; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-bidi-theme-font: minor-latin; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-bidi-font-style: italic;">Results show that the meditation-based technique for stillness used in this study enhances aspects of pupils well-being. This is supported by the fact that at one of the schools where this study was done the stillness practice is now mandatory. Every class practices scheduled stillness several times a week and the pupils frequently asks for extra practices before examinations and other stress related events. Other schools in the city also have started this practice.